STRATEGI PELESTARIAN TRADISI JAMASAN PUSAKA SUROLOYO SEBAGAI ASET BUDAYA TRADISIONAL DI KULON PROGO YOGYAKARTA - Sarbini, Sarbini; Hapsari, Indri Shaila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
This research aims to determine the strategy for preserving the Jamasan Pusaka tradition, the roles of the community and the government, and what obstacles are faced in the effort to preserve the Jamasan Pusaka Tradition. The research method uses qualitative research and data analysis using SWOT analysis. Based on the research conducted, the researcher found that the preservation of the Jamasan Pusaka tradition in Suroloyo is the only Jamasan Pusaka tradition that is in Kulon Progo. In addition, this tradition is carried out at the Puncak Suroloyo Tourism Object on the first of Suro with promotional efforts to attract tourists to witness. In an effort to preserve the jamasan heritage tradition, it can be said that it is good because the surrounding community is still carrying out this tradition until now and especially this event has been promoted in various media, both social media and print media so that tourists who don't know can watch it. In addition, the community plays an important role in the Jamasan Pusaka Tradition event where the community still carries out this tradition until now and the Government is very helpful. The obstacle in preserving the Jamasan Pusaka Tradition is because many young people, both the community and tourists, do not know what the purpose, potential, and heirlooms are used in this traditional event. Keywords: Jamasan Pusaka Tradition, Preservation, Culture, SWOT Analysis